Application of Debate Learning System in Collaboration with Time Token Arend to Improve Thinking Ability and Student Learning Result - Ana, Emy Fitri (Unversitas Negeri Malang, 2017)
In education the role of teachers is needed as a facilitator, especially in the curriculum in 2013 requires students to be more active in the process of learning is not just focus on the teacher, but students also play an active role in learning.The purpose of this study to improve students' critical thinking skills and student learning outcomes, especially on economic subjects class XI IPS 6J3 SMAN 10 Malang. This study was conducted 2 cycles, each cycle consisted of 3 meetings. Data collection was done by using observation method, interview, test, field note, and questionnaire.Based on the results of the research can be seen that there is an increase in learning outcomes and critical thinking skills students have applied the model of learning debate collaborate with time token arend. This can be shown the learning outcomes in the cognitive domain of the percentage cycle I 12 students complete (33%), while the second cycle of 31 students complete (86%). In critical thinking ability also experience improvement of the cycle I 5 students complete (14%), while cycle II 31 student complete (86%). Percentage of the implementation of research activities in cycle I 76% in 92% cycle II also increased.Â Keywords: Debate Learning, Time Token Arend, Thinking Ability, Learning Result.